Penerapan Yellow Box Junction Pada Perlintasan Sebidang Untuk Mengurai Antrian Kendaraan Akibat Penutupan Pintu Perlintasan Sebidang - Putra, I Dewa Gede Tantara Tesa; Purwanto, Edi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2018)
Good transportation is smooth, safe, safe, convenient and efficient transportation. In order to realizesuch good transportation, effort is needed in overcoming various transportation problems that existtoday and then do various further development. One of the transportation problems is the locationof the intersection of Jalan Teuku Umar by crossing a plot of KS Tubun Road between the road andthe railroad track. The crossing of this plot resulted in congestion in the aftermath of the closure ofthe railway crossing. This is very dangerous and causes a burden of loss if there is a train thatpasses at close intervals due to the unraveling of congestion that occurred on Jalan Teuku Umar.The method in this research is research and development. In this research, the research location isTeuku Umar Street. The data collection is divided into primary data and secondary data. Primarydata were obtained by directly conducting a survey to a research site on Jalan Teuku Umar. Theobservation period in the field is done on Sunday, 17 September 2017 for 14 hours from 06.00 to20.00 WIB. Secondary data is data sourced from institutions - insatansi related to research that isPT. Kereta Api Indonesia on the schedule of passenger trains and freight passing through a planeof Teuku Umar Street. Based on the analysis of the application of yellow box junction at theintersection can decompose the queue length that occurs on Teuku Umar Street.